Shaping Green Purchase Intention: How Attitude, Norms, Environmental Awareness, and Knowledge Interact - Putu Chyntia Ayu Devani; Ida Nyoman Basmantra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2026)
This study investigates key determinants of green purchase intention among Indonesian youth by applying an extended Theory of Planned Behaviour (TPB) that integrates attitude toward green products, subjective norms, environmental concern, and environmental knowledge. A quantitative, cross-sectional survey was administered online to purposively selected respondents in Jakarta, Bandung, and Bali (n = 210), measured using a five-point Likert scale. The indicators captured attitude (ATT1–ATT3), subjective norms (SN1–SN2), environmental concern (EC1–EC3), environmental knowledge (EK1–EK4), and green purchase intention (GP1–GP3). Data were analysed using Partial Least Squares–Structural Equation Modeling (PLS-SEM), including measurement-model evaluation (outer loadings > 0.701; AVE = 0.581–0.753; composite reliability = 0.844–0.868) and structural testing via bootstrapping. The structural results show that attitude exerts the strongest positive effect on green purchase intention (β = 0.377; t = 5.230; p < 0.001; f² = 0.160), followed by environmental concern (β = 0.280; t = 3.610; p < 0.001; f² = 0.080) and environmental knowledge (β = 0.204; t = 2.675; p = 0.004; f² = 0.040). In contrast, subjective norms are not significant (β = 0.035; t = 0.482; p = 0.315; f² = 0.002). The model explains substantial variance in green purchase intention (R² = 0.642; adjusted R² = 0.635). Theoretically, the findings refine extended TPB in a developing-country context by demonstrating the primacy of internal cognitive–affective drivers over social pressure for urban youth. Practically, firms and policymakers should prioritize attitude-building communication, environmental education, and credible green information to strengthen intention formation. Overall, this study highlights that strengthening consumers’ attitudes, concern, and knowledge is pivotal to accelerating sustainable purchasing intentions in Indonesia.